PENGELOLAAN DAN TINGKAT KESEJAHTERAAN GAJAH SUMATERA (Elephas maximus sumatranus Temminck, 1847) DI FLYING SQUAD WWF TAMAN NASIONAL TESSO NILO RIAU - Tohir, Rizki Kurnia; Mustari, Abdul Haris; Masy'ud, Burhanuddin (Media Konservasi, 2017)
Conflict between human and elephants in Tesso Nilo National Park encourages WWF to establish the Flying Squad. Related to the function of the sumatran elephants in Flying Squad as the patrol team, it is necessary to conduct a proper management to ensure animal welfare. This study aims to examine the aspects of welfare management and asses the level of welfare of sumatran elephants in Flying Squad. The research methodology used for this study are literature review, interviews and field observation. Data analyzed by describing the suitability of management and tabulating the assessment. The management of cages, feed, health and reproduction requires some improvements such as the type, number and equipment of the cages, natural feed adequacy, medical infrastructure and reproduction management. The 76,98% percentage rate of sumatran elephant welfare, which is relatively good, is because there are only 14 priority components of 43 components of animal welfare assessment that need improvements and enhanced management. Keywords: animal welfare, flying squad, the patrol elephant